Guest-triggered "Soma–Iwamoto-type" penetration complex Fe(4-methoxypyrimidine)2[M(CN)2]2·Guest (M = Ag, Au). Issue 9 (8th February 2023) - Kitase, Kosuke; Akahoshi, Daisuke; Kitazawa, Takafumi
Abstract : We synthesized novel "Soma–Iwamoto-type" complexes that contain the 4-methoxypyrimidine ligand. The guest clathrate complexes demonstrate the SCO phenomenon and interesting rarely reported penetrated structures with two Soma–Iwamoto-type structures. Abstract : Many laboratories have performed extensive studies on the spin-crossover (SCO) phenomenon. Herein, we synthesized novel "Soma–Iwamoto type" complexes containing a 4-methoxypyrimidine (4-MeOPmd) ligand, i.e., Fe(4-MeOPmd)2 [Ag(CN)2 ]2 (1Ag ), Fe(4-MeOPmd)2 [Au(CN)2 ]2 (1Au ), and Fe(4-MeOPmd)2 [Ag(CN)2 ]2 ·0.25(4-MeOPmd) (1Ag·0.25G ). Moreover, we synthesized a 4, 6-dimethoxypyrimidine (4, 6-diMeOPmd) clathrate complex, i.e., Fe(4-MeOPmd)2 [Ag(CN)2 ]2 ·0.25(4, 6-diMeOPmd) (2Ag·0.25G ) and Fe(4-MeOPmd)2 [Au(CN)2 ]2 ·0.25(4, 6-diMeOPmd) (2Au·0.25G ). Some of these complexes, i.e., 1Ag·0.25G, 2Ag·0.25G, and 2Au·0.25G, demonstrated penetrated structures, which are very interesting given that they have rarely been reported to date. 1Au and 1Ag did not show the SCO phenomenon, 1Ag·0.25G showed a gradual multi-step SCO phenomenon, and 2Au·0.25G and 2Ag·0.25G showed an abrupt half SCO phenomenon.